+0  
 
0
42
1
avatar

Let \(f(x) = Ax + B\) and \(g(x) = Bx + A\), where \(A \neq B\). If \(f(g(x)) - g(f(x)) = B - A\), what is \(A + B\)?

 Mar 26, 2020
 #1
avatar+20768 
0

f(x)  =  Ax + B           g(x)  =  Bx +A          A <> B

 

f( g(x) )  =  f( Bx + A)  =  A(Bx + A) + B  =  ABx + A2 + B

 

g( f(x) )  =  g( Ax + B )  =  B(Ax + B) + A  =  ABx + B2 + A

 

f( g(s) ) - g( f(x) )  =  [ ABx + A2 + B ] - [ ABx + B2 + A ]  =  ABx + A2 + B - ABx - B2 - A  =  A2 - B2 + B - A

 

Since f( g(s) ) - g( f(x) )  =  B - A

              A2 - B2 + B - A  =  B - A 

                           A2 - B2  =  0

                (A + B)(A - B)  =  0

 

Either  A + B  =  0

      or   A - B  =  0     --->     A  =  B        (but this is impossible because the problem states that A <> B)

 

So:  A + B  =  0

 Mar 26, 2020

25 Online Users

avatar
avatar
avatar
avatar